Francesco Vietti, Hotel Albania: Viaggi, migrazioni, turismo, Roma, Carocci, 2011, pp. 193 - Antonio Maria Pusceddu (Anuac, 2015)
Book review of Francesco Vietti, Hotel Albania: Viaggi, migrazioni, turismo, Roma, Carocci, 2011, pp. 193.